Rehabilitation delivery models to foster healthy ageing—a scoping review - Seijas, Vanessa; Maritz, Roxanne; Fernandes, Patricia; Bernard, Renaldo M.; Lugo, Luz Helena; Bickenbach, Jerome; Sabariego, Carla (Frontiers in Rehabilitation Sciences, 2024)
Introduction Rehabilitation is essential to foster healthy ageing. Older adults have unique rehabilitation needs due to a higher prevalence of non-communicable diseases, higher susceptibility to infectious diseases, injuries, and mental health conditions. However, there is limited understanding of how rehabilitation is delivered to older adults. To address this gap, we conducted a scoping review to describe rehabilitation delivery models used to optimise older adults' functioning/functional ability and foster healthy ageing. Methods We searched Medline and Embase (January 2015 to May 2022) for primary studies published in English describing approaches to provide rehabilitation to older adults. Three authors screened records for eligibility and extracted data independently and in duplicate. Data synthesis included descriptive quantitative analysis of study and rehabilitation provision characteristics, and qualitative analysis to identify rehabilitation delivery models. Results Out of 6,933 identified records, 585 articles were assessed for eligibility, and 283 studies with 69,257 participants were included. We identified six rehabilitation delivery models: outpatient (24%), telerehabilitation (22%), home (18.5%), community (16.3%), inpatient (14.6%), and eldercare (4.7%). These models often involved multidisciplinary teams (31.5%) and follow integrated care principles (30.4%). Most studies used a disease-centred approach (59.0%), while studies addressing multimorbidity (6.0%) and prevalent health problems of older adults, such as pain, low hearing, and vision, or incontinence were scarce. The most frequently provided interventions were therapeutic exercises (54.1%), self-management education (40.1%), and assessment of person-centred goals (40%). Other interventions, such as assistive technology (8.1%) and environmental adaptations (7.4%) were infrequent. Conclusions Focusing on primary studies, this scoping review provides an overview of rehabilitation delivery models that are used to foster healthy ageing and highlights research gaps that require further attention, including a lack of systematic assessment of functioning/functional ability, a predominance of disease-centred rehabilitation, and a scarcity of programmes addressing prevalent issues like pain, hearing/vision loss, fall prevention, incontinence, and sexual dysfunctions. Our research can facilitate evidence-based decision-making and inspire further research and innovation in rehabilitation and healthy ageing. Limitations of our study include reliance on published research to infer practice and not assessing model effectiveness. Future research in the field is needed to expand and validate our findings.